Bevacizumab as a treatment for radiation necrosis of brain metastases post stereotactic radiosurgery - Boothe, Dustin (Oxford University Press, 2013)
BACKGROUND: Cerebral radiation necrosis (RN) is a difficult to treat complication of stereotactic radiosurgery (SRS) that can result in progressive neurologic decline. Currently, steroids are the standard of care treatment for brain RN despite their adverse effect profile and limited efficacy. The purpose of this study was to evaluate the treatment efficacy of cerebral RN to bevacizumab in patients with brain metastases previously treated with SRS. METHODS: We retrospectively reviewed 14 lesions in 11 patients treated with bevacizumab for brain RN secondary to SRS for their brain metastases. Steroid dosing, RN-associated symptoms, and magnetic resonance imaging (MRI) scans were examined before, during, and after bevacizumab administration. RESULTS: Of the 11 patients included, 6 had metastatic non–small cell lung cancer, and 5 had metastatic breast cancer. The mean percentage decrease in RN volume seen on T1 post-Gadolinium and fluid-attenuated inversion recovery (FLAIR) MRI at first follow-up, at a mean of 26 days (range, 15–43 days), was 64.4% and 64.3%, respectively. MRI changes were sustained on follow-up MRI scans, obtained at a mean of 33 days (range, 7–58 days) after bevacizumab discontinuation. After bevacizumab treatment, all patients initially receiving steroids had a reduction in steroid requirement, and all but one had an improvement in or stability of RN-associated symptoms. No patients experienced intratumoral bleeds or other adverse effects related to their bevacizumab treatment. CONCLUSIONS: Bevacizumab is effective and safe for the treatment of RN after SRS for brain metastasis. In this context, bevacizumab offers symptomatic relief, a reduction in steroid requirement, and a dramatic radiographic response.